2010
DOI: 10.1038/hr.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

A46G and C79G polymorphisms in the β2-adrenergic receptor gene (ADRB2) and essential hypertension risk: a meta-analysis

Abstract: No consensus has been reached on the association between the b2-adrenergic receptor polymorphisms A46G and C79G and essential hypertension risk. We performed a meta-analysis to confirm the possible association. After reviewing 303 reports in PubMed and 359 reports in Embase, we included in our meta-analysis 18 articles (20 studies) that met our inclusion criteria. The fixed-effects model and the random-effects model were applied for dichotomous outcomes to combine the results of the individual studies. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
2
12
0
2
Order By: Relevance
“…17,18 Upon examining the association results separately by panel, we found that the direction and strength of the associations with BP traits were almost concordant for the two SNPs; that is, CYP11B2 rs1799998 and AGT rs699 (Supplementary Table 1). In addition, we found significant associations of ADRB2 rs1042713 and ACE rs4341 with SBP (P ¼ 0.004 for rs4341), DBP (P ¼ 0.005 for rs1042713 and P ¼ 0.0118 for rs4341), and/or hypertension (P ¼ 0.008 for rs1042713 and P ¼ 0.002 for rs4341) in the CAGE study panel 3, in directions that were consistent with those of previous studies; 16,27,28 however, these associations were not replicable in panel 1 and panel 2 (Supplementary Table 1). …”
Section: P-valuesupporting
confidence: 79%
See 3 more Smart Citations
“…17,18 Upon examining the association results separately by panel, we found that the direction and strength of the associations with BP traits were almost concordant for the two SNPs; that is, CYP11B2 rs1799998 and AGT rs699 (Supplementary Table 1). In addition, we found significant associations of ADRB2 rs1042713 and ACE rs4341 with SBP (P ¼ 0.004 for rs4341), DBP (P ¼ 0.005 for rs1042713 and P ¼ 0.0118 for rs4341), and/or hypertension (P ¼ 0.008 for rs1042713 and P ¼ 0.002 for rs4341) in the CAGE study panel 3, in directions that were consistent with those of previous studies; 16,27,28 however, these associations were not replicable in panel 1 and panel 2 (Supplementary Table 1). …”
Section: P-valuesupporting
confidence: 79%
“…[14][15][16][17][18][19][20] Compared with Japanese samples genotyped in this study, the relative increase in joint meta-analysis samples appeared to be modest (that is, 5-40%) at all loci except AGT rs699 for SBP/DBP association, whereas this increase was prominent (that is, 105-586%) for hypertension association, thereby providing the joint meta-analysis, in particular, for case-control study (5757-17399 cases vs. 11240-23338 controls) with reasonable power. For SBP and DBP, there were significant associations (two-tailed Po0.012, putative risk-allele homozygote vs. non-risk-allele homozygote) with AGT rs699 (P ¼ 0.001 for SBP), CYP11B2 rs1799998 (P ¼ 2.0 Â 10 À6 for SBP; P ¼ 3.1 Â 10 À6 for DBP), and ACE rs4340 (P ¼ 0.01 for DBP) (Supplementary Table 2).…”
Section: Joint Meta-analysis For Seven Candidate Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…'s study [21], [23] was higher than our current study, we considered that C79G polymorphism might associate with more severe hypertension. Our previous meta-analysis [27] also found the similar results, which suggested that C79G polymorphism was associated with ‘severe hypertension' defined on SBP≥160 mmHg and/or DBP≥95 mmHg, but no significant association could be found based on the current clinical diagnostic standard of hypertension on SBP≥140 mmHg and/or DBP≥90 mmHg [2]. Interestingly, further research was conducted to compare with Gu et al and Ge et al .…”
Section: Discussionsupporting
confidence: 60%